Doing your masters dissertation : realizing your potential as a social scientist - Hart, Chris (New Delhi : Sage publications, 2005)
"Doing Your Masters Dissertation: Realizing Your Potential as a Social Scientist" is a comprehensive guide for master's students in the social sciences. It offers a structured, step-by-step approach to the dissertation process, covering everything from topic selection and research design to data presentation and writing. The book emphasizes practical advice, incorporating worked examples and guidelines for further reading. It also addresses crucial elements like ethical considerations and assessment criteria. This accessible resource provides up-to-date reference materials, both print and electronic, making it an invaluable tool for postgraduate students navigating the complexities of dissertation writing. Its student-focused approach and clear explanations make it an essential companion for successfully completing a master's level dissertation.
Includes bibliographical references (p. 461-472) and index.
Keywords: Dissertation process; Designing the research; Research question; Collecting and analyzing data